Managing your assets in the publication economy - Ulf Kronman (Linköping University Electronic Press, 2013)
The issue this article aims to address is the fact that publications may nowadays be used to assess impact and quality of research in ways academics may not be fully aware of. During recent years, scholarly publications have gained in importance, not primarily as the traditional vehicle for the dissemination of new scientific findings, but as a foundation for assessing the production and impact of organizations, research groups and individual researchers. This means that publications as artefacts per se are starting to play a new important role in the scientific community and that researchers need to be aware of how publication and citation counts are being used to assess their research and the outreach, impact and reputation of their mother organization. University rankings, for instance, often have some parameters based on the publishing of the ranked institution. This article is thus not about scientific writing as such; it focuses on what happens to your publication after the publishing has taken place and on aspects to take into account while planning the publishing of your article, report or book.